Challenges in Self-organizing within Scrum Teams: Theory Evaluation and Recommendations Based on Scrum Practitioners - Lyngfelt,Boman; Elhemaily,Ahmad (2019)
Being self-organizing is a core element of successful Scrum teams. Such teams require a high level of autonomy to perform, yet they operate within the context of an organization and its rules. Scrum teams should decide their work process, what to work on and how to deliver value for customers. The existing literature on Scrum teams investigates the challenges Scrum teams face in their daily life or the challenges teams face when transforming their work process from traditional product development (such as waterfall) to agile product development (such as Scrum). However, little is known about the challenges and impediments that directly relate to and threaten the self-organizing nature of Scrum teams. Through a mixed method approach inspired by grounded theory elements, this study compares the challenges acknowledged in the literature with the practical experience of Scrum practitioners. The study presents expert knowledge from 13 interviewed Scrum masters in various European countries as well as 65 questionnaire respondents (Scrum practitioners) from all around the world. The study then presents recommendations based on these practitioners’ expert views. The recommendations are aimed towards future Scrum teams to help them mitigate and possibly prevent challenges that could possibly threaten their efforts towards being self-organizing.
Keywords: Scrum; Self-organizing; agile; product management; software development